PENGARUH AUDIT TENURE DAN UKURAN KAP TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2013-2015) - Candra Jimmi Michael; Abdul Rohman (Diponegoro Journal of Accounting, 2017)
This research aims examine the influence of audit tenure and size of public accountant to audit report lag (ARL), and the auditor industry specialization as moderating variable between audit tenure and audit report lag (ARL).The populations in this study are all manufacture companies listed in Indonesian Stock Exchange in years 2013-2015. Sampling method in this study is purposive sampling. Data used in this research are secondary data from financial statement and independent auditor’s report of manufacture companies. The total sample in this study are 52 firms. Analysis technique that used in this study is multiple linear regression.The empirical result of this study show that audit tenure have significant effect on audit report lag (ARL). auditor industry specialization does not weaken the effect of audit tenure to audit report lag (ARL). the size of public accountant has not significant effect to audit report lag.